Low-dose topiramate and hydrochlorothiazide-associated early acute myopia and angle narrowing: A case report - Wu, Chao; Pan, Hong; Feng, Shijun; Wang, Xiaokun; Liu, Zhaoqiang; Zhao, Bojun (Frontiers in Medicine, 2023)
Purpose: To report a unique case of topiramate and hydrochlorothiazide associated with acute myopia and angle narrowing. Patients: and Methods A 34-year-old Asian woman presented with prominent binocular visual acuity decrease, 6 hours after taking only one dose of 25mg topiramate, 25mg hydrochlorothiazide, and 22.4mg fluoxetine to lose weight. She was subsequently diagnosed with acute bilateral myopia and angle narrowing and started on topical therapy. Results: Initial examination revealed a decreased visual acuity of 20/100 bilaterally, an elevated intraocular pressure of 23mmHg in the right eye and 24mmHg in the left eye, the suprachoroidal effusions, and the angle narrowing. After discontinuation of these drugs and the use of topical therapy, the patient made a full recovery. Conclusion: We speculate that there is a drug-drug interaction of topiramate and hydrochlorothiazide that may lead to the angel narrowing in a short time and low dose. Discontinuation of the drug timely usually leads to complete recovery within days to weeks.